Insulin resistance and dyslipidemia in low-birth-weight goat kids - Song, Huihui; Hao, Zhuohang; Feng, Hehan; Li, Rui; Zhang, Ran; Limesand, Sean W.; Zhao, Yongju; Chen, Xiaochuan (Frontiers in Veterinary Science, 2024)
Low birth weight (LBW) impairs the development and health of livestock by affecting postnatal growth performance and metabolic health in adulthood. Previous studies on indigenous goats in Southwest China showed that LBW goat kids had higher mortality and morbidity rates, including hepatic dyslipidemia and liver damage. However, mechanism of insulin resistance affecting lipid metabolism under LBW conditions remains unclear. In this study, we conducted in vivo glucose-insulin metabolic studies, measured biochemical parameters, and analyzed related regulatory pathways. Both glucose tolerance tests and insulin tolerance tests indicated insulin resistance in LBW goat kids compared to controls (P < 0.05). The marker of insulin resistance, homeostasis model assessment (HOMA), was 2.85-fold higher in LBW than control goats (P < 0.01). Additionally, elevated levels of free fatty acids in both plasma and skeletal muscle were observed in LBW goats compared to normal birth weight (NBW) goats (P < 0.05). Transcriptome analysis disclosed impairments in lipid metabolism and insulin signaling in LBW goats. The observed lipid accumulation was associated with the upregulation of genes linked to fatty acid uptake and transport (FABP3), fatty acid oxidation (PPARA), triacylglycerol synthesis (LPIN1 and DGAT1), oxidative stress (ANKRD2), and insulin resistance (PGC1α). Furthermore, the insulin receptor substrate 2 (IRS2) were lower in the liver from LBW goat kids (P < 0.05). While there is no change in insulin function in skeletal muscle, LBW may lead to lipid accumulation in skeletal muscle by interfering insulin function in the liver. These findings collectively impact the health and growth performance of livestock.